Coconut-water as fermentation medium for enzyme production (1): Factor analysis in batch shake-flask fermentation - Jailani Salihon,; Jamaliah Md. Jahim,; Ahmad Jaril Asis, (1995)
Factor analysis was applied to batch shake-flask fermentations for the production of the enzyme cytochrome p-450 by the yeast Saccharomyces cerevisiae NCYC. 754 on a medium based on coconut-water allowing a screening of the experimental variables temperature (T), pH, shaking rate (RPM) and the initial concentrations of glucose (G), yeast extract (YE), peptone (P) and phosphoric acid (PA)supplements. Both the enzyme specific yield (nmol g-1) and the biomass yield (gL-1) were found to be strongly influenced by all the above experimental variables except P. Previous media formulations for the fermentation have shown that peptone is very important in ensuring good growth and enzyme production. The possibility of formulating a coconut-water based medium which needs less peptone supplement would lower medium costs as well as partly solve the wastewater treatment problem of the coconut processing plants